2008
DOI: 10.1073/pnas.0710954105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular links among the causative genes for ocular malformation: Otx2 and Sox2 coregulate Rax expression

Abstract: The neural-related genes Sox2, Pax6, Otx2, and Rax have been associated with severe ocular malformations such as anophthalmia and microphthalmia, but it remains unclear as to how these genes are linked functionally. We analyzed the upstream signaling of Xenopus Rax (also known as Rx1) and identified the Otx2 and Sox2 proteins as direct upstream regulators of Rax. We revealed that endogenous Otx2 and Sox2 proteins bound to the conserved noncoding sequence (CNS1) located Ϸ2 kb upstream of the Rax promoter. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 40 publications
5
112
1
Order By: Relevance
“…In a similar way, we observed mild or no cooperation between Sox2 and Pax6 or Otx2 on Six3.2 regulation (Fig. 3, F and G), in contrast to reports for other target genes (40,41). Furthermore, we could not find a previously proposed Six3 autoregulation (25,42), neither with Six3.2 nor with its Six3.1 paralog or their mammalian orthologue (Fig.…”
Section: Dose-response Luc Assays Confirmed Several Trs Candidates Ascontrasting
confidence: 48%
“…In a similar way, we observed mild or no cooperation between Sox2 and Pax6 or Otx2 on Six3.2 regulation (Fig. 3, F and G), in contrast to reports for other target genes (40,41). Furthermore, we could not find a previously proposed Six3 autoregulation (25,42), neither with Six3.2 nor with its Six3.1 paralog or their mammalian orthologue (Fig.…”
Section: Dose-response Luc Assays Confirmed Several Trs Candidates Ascontrasting
confidence: 48%
“…Sox2 and Otx2 are able to interact directly via their HMG and homeobox DNA-binding domains, respectively (Danno et al, 2008), and Otx2 has been shown to suppress the expression of Sox2 during retinal differentiation (Nishihara et al, 2012). The widespread ectopic expression of Sox2 in the cochlear duct of Pax2Cre-Otx2 mutant mice may suggest that it acts as a permissive prosensory factor allowing ectopic expression of Jag1 and p27 kip1 , which eventually generate an ectopic organ of Corti in the nonsensory region usually characterized by Otx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the subcellular localizations of the xRipply3 proteins, COS7 cells were transfected with 200 ng of pCS2-HA-xRipply3, and immunocytochemistry was performed as described previously (Danno et al, 2008) with an anti-HA antibody (Y-11; Santa Cruz Biotechnology).…”
Section: Cell Culturing Luciferase Assays Subcellular Localization mentioning
confidence: 99%